2017
DOI: 10.1089/neu.2016.4508
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptom Modeling in Male and Female C57BL/6J Mice after Experimental Traumatic Brain Injury

Abstract: Psychiatric symptoms such as anxiety and depression are frequent and persistent complaints following traumatic brain injury (TBI). Modeling these symptoms in animal models of TBI affords the opportunity to determine mechanisms underlying behavioral pathologies and to test potential therapeutic agents. However, testing these symptoms in animal models of TBI has yielded inconsistent results. The goal of the current study was to employ a battery of tests to measure multiple anxiety- and depressive-like symptoms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 112 publications
15
72
1
Order By: Relevance
“…Other groups have used in-depth behavioral studies to study sex-differences after preclinical TBI. Similar to our findings, Tucker et al demonstrated that female mice had a similar lesion volume to male mice 30 d after CCI, and presented with similar behavioral deficits in the Morris Water maze and rotarod test, although female mice display fewer anxiety-like behaviors after CCI (Tucker et al 2017; Tucker et al 2016). Other studies have found that female rates have better motor ability following TBI compared to males (Roof et al 1993; Wagner et al 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other groups have used in-depth behavioral studies to study sex-differences after preclinical TBI. Similar to our findings, Tucker et al demonstrated that female mice had a similar lesion volume to male mice 30 d after CCI, and presented with similar behavioral deficits in the Morris Water maze and rotarod test, although female mice display fewer anxiety-like behaviors after CCI (Tucker et al 2017; Tucker et al 2016). Other studies have found that female rates have better motor ability following TBI compared to males (Roof et al 1993; Wagner et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have revealed that the estrous cycle stage at the time of the injury has no effect on post-injury neuroprotection of female mice and rats (Bramlett and Dietrich 2001; Monaco et al 2013). In addition, when TBI was induced at random stages of the estrous cycle the performance variability was similar to that reported in male mice (Tucker et al 2017; Tucker et al 2016). …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, anxiety measurements in mice/rats after TBI using the open field test are to date inconclusive (Malkesman et al, 2013). Mice decrease their traverse of the center distance traveled in severe, but not mild, injury (Tucker et al, 2017); our animals more likely fall into the mild injury category.…”
Section: Behavioral Impairments and Relation To Clinical Studiesmentioning
confidence: 82%
“…Depressed animals can exhibit futility (e.g., Crawley, 1999;Porsolt, Anton, Blavet, & Jalfre, 1978). Results regarding behavioral despair in mice/rats after TBI using the more aversive swim test or tail suspension test, however, are inconclusive or negative (Malkesman, Tucker, Oz, & McCabe, 2013;Tucker, Burke, Fu, & McCabe, 2017). The open field test would not be called aversive, so the reduction in rearing may be related to something else.…”
Section: Behavioral Impairments and Relation To Clinical Studiesmentioning
confidence: 99%